Multilevel Cortical Processing of Somatosensory Novelty: A Magnetoencephalography Study - Naeije, Gilles; Vaulet, Thibaut; Wens, Vincent; Marty, Brice; Goldman, Serge; De Tiège, Xavier (Frontiers in Human Neuroscience, 2016)
Using magnetoencephalography (MEG), this study investigates the spatio-temporal dynamics of the multilevel cortical processing of somatosensory change detection. Neuromagnetic signals of sixteen healthy adult subjects (7 females and 9 males, mean age 29 +/-3 y) were recorded using whole-scalp-covering MEG while they underwent an oddball paradigm based on simple standard (right index fingertip tactile stimulation) and deviant (simultaneous right index fingertip and middle phalanx tactile stimulation) stimuli gathered into sequences to create and then deviate from stimulus patterns at multiple (local versus global) levels of complexity. Five healthy adult subjects (3 females and 2 males, mean age 31,6 +/-2 y) also underwent a similar oddball paradigm in which standard and deviant stimuli were flipped. Local deviations led to a somatosensory mismatch response peaking at 55-130 ms post-stimulus onset with a cortical generator located at the contralateral secondary somatosensory cortex. The mismatch response was independent of the deviant stimuli physical characteristics. Global deviants led to a P300 response with cortical sources located bilaterally at temporo-parietal junction (TPJ) and supplementary motor area (SMA). The posterior parietal cortex (PPC) and the SMA were found to generate a contingent magnetic variation (CMV) attributed to top-down expectations. Amplitude of mismatch responses were modulated by top-down expectations and correlated with both the magnitude of the CMV and the P300 amplitude at the right TPJ. These results provide novel empirical evidence for a unified sensory novelty detection system in the human brain by linking detection of salient sensory stimuli in personal and extra-personal spaces to a common framework of multilevel cortical processing.